PENGARUH SOSIALISASI PERPAJAKAN, PERILAKU APARAT PAJAK, SISTEM ADMINISTRASI PAJAK MODERN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM (Survei pada UMKM Pengrajin Kayu di Pasar Mebel Gilingan Surakarta) - Aprilyani, Faradina Wahyu; Harimurti, Fadjar; Widarno, Bambang (Universitas Slamet Riyadi, 2021)
This study aims to determine the effect of tax socialization, the behavior oftax officials, modern tax administration systems, and tax sanctions on SMEtaxpayer compliance. The type of data used is quantitative data. The data sourceused is primary data. The technique of collecting data is by distributingquestionnaires in the Gilingan Furniture Market in Surakarta. The population ofthis research is 74 UMKM. The sample taken in this study were 61 respondents.The sampling technique was purposive sampling. This study shows the results thatthe socialization of taxation has a significant negative effect on UMKM taxpayercompliance, the behavior of tax officials has a significant negative effect onUMKM taxpayer compliance, modern tax administration systems have asignificant negative effect on UMKM taxpayer compliance and tax sanctions havea significant positive effect on UMKM taxpayer compliance.